Problems of Measuring Energy Poverty - Pawliczek, Ewa (Problemy pomiaru ubóstwa energetycznego, 2023)
Energy poverty is a very important social problem, especially in the present economic and geopolitical situation. The aim of the article is to systematize the existing knowledge in the field of measurement and evaluation of this phenomenon, with particular emphasis on multidimensional measures of energy poverty. The author of the study, basing on literature sources, attempts to identify, and classify measures of energy poverty, and characterizes its various dimensions and aspects. As the analyses show, in recent years significant progress has been made in the methodology of measuring this phenomenon, including new approaches that consider the multidimensional measurement of energy poverty.
Współczesne problemy społeczno-ekonomiczne w ujęciu analitycznym / pod red. Agnieszki Stanimir. - Wrocław, 2023, s. 61-73
Keywords: energy poverty; energy poverty indicators; energy poverty measures; ubóstwo energetyczne; wskaźnik ubóstwa energetycznego; miary ubóstwa energetycznego